Image processing and communications challenges 10 : 10th International Conference, IP&C'2018 Bydgoszcz, Poland, November 2018, proceedings /: 10th International Conference, IP&C'2018 Bydgoszcz, Poland, November 2018, proceedings. ([2019]) - Unknown
No abstract available